Kobiety w spółdzielczości – od pani domu do masowej aktywizacji zawodowej (1935–1989/1990) - Chyra-Rolicz, Zofia (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2014)
This paper shows the long way for popularization co-operative movement among Polish women from different social class in the first half of XX c. up to the end of so called time of real socialism. The feminine organization – League of Co-operators in Poland – was establish in 1935 as results of many earlier efforts concerning co-operative assistance in everyday housekeeping, education of children and cultural activity. It was oriented towards help for housekeepers, modernization their private housekeeping in the cities and countryside. It had begun thinking about housekeeping as a serious part of national economy. During the second world war the women organization had worked in the underground in legal acting union of consumer co-operatives. It organized many thousands courses and trainings for women, especially in countryside, concerning the modern housekeeping. It supported also the patriotic, liberating activity and resistant movement different political orientations. After the second world war Polish co-operatives had token very important role in the national economy as the sector of socialist social economy. Co-operatives had taken part in the realization economical and social policy of state and communist’s party the mass women professional activity, taking them places of work and helping in duties of housekeepers and employees.